EXPLORING STUDENTS’ CHALLENGES IN IMPLEMENTING PROJECT- BASED LEARNING IN TEFL CLASS - Nurlaila Husain; Sri Widyarti Ali (International Journal of Teaching and Learning, 2025)
This study investigates the challenges faced by students in implementing Project- Based Learning (PjBL) in the Teaching English as a Foreign Language (TEFL) course within the English Education Study Program. Using a descriptive qualitative approach, data were collected through questionnaires given to ten TEFL students with PjBL experience. Results show that limited knowledge of PjBL concepts, inconsistent lecturer guidance, and restricted resources contribute to student difficulties, reducing motivation and learning outcomes. The study suggests the need for clearer instructional support, improved facilities, and structured guidance to optimize the effectiveness of PjBL in language education.